The Effect Of Work Motivation, Work Environment, Compensation In Improving Employees' Work Ethos - Meita Pragiwani; Raja Bran Hans (Universitas Dharma Wacana, 2022)
This study aims to determine and analyze the effect of work motivation (X1), Work Environment (X2) and compensation (X3) in an effort to improve the work ethic (Y) of employees in East Jakarta and be able to provide empirical evidence on the effect between variables X and Y variables. This study uses an associative research type with a casual relationship with a quantitative approach, which is measured using the SEM-PLS method using Excel and SmartPLS3.0 software. The sample of this study was measured using the Slovin sampling technique with an error rate of 10%, thus obtaining a sample of 100 employees. The data used in this study are primary data with data collection techniques using questionnaires via google form. The result of variable X1 to Variable shows that there is a positive and significant effect, this indicates that the higher and increasing the motivation variable, the employee's work ethic is increasing. Meanwhile, the X2 and X3 variables have a positive or unidirectional effect on the Y variable, but it is not significant. As for the empirical evidence, the X1 variable (Work Motivation) is worth 0.674 67.4% against Y while for the X2 variable (Work Environment) it is 0.169 16.9% against Y and for the X3 variable is 0.169 16.9% on work ethic